Augmented Reality for Head and Neck Carcinoma Imaging: Description and Feasibility of an Instant Calibration, Markerless Approach. (March 2021) - Gsaxner, Christina; Pepe, Antonio; Li, Jianning; Ibrahimpasic, Una; Wallner, Jürgen; Schmalstieg, Dieter; Egger, Jan
Highlights: We present a novel augmented reality system for head and neck carcinoma imaging. We emphasize usability by adopting automatic registration and calibration. Immersive visualization through a head mounted display improves perception of data. Medical experts accepted our application in a real clinical scenario. Abstract: Background and Objective: Augmented reality (AR) can help to overcome current limitations in computer assisted head and neck surgery by granting "X-ray vision" to physicians. Still, the acceptance of AR in clinical applications is limited by technical and clinical challenges. We aim to demonstrate the benefit of a marker-free, instant calibration AR system for head and neck cancer imaging, which we hypothesize to be acceptable and practical for clinical use. Methods: We implemented a novel AR system for visualization of medical image data registered with the head or face of the patient prior to intervention. Our system allows the localization of head and neck carcinoma in relation to the outer anatomy. Our system does not require markers or stationary infrastructure, provides instant calibration and allows 2D and 3D multi-modal visualization for head and neck surgery planning via an AR head-mounted display. We evaluated our system in a pre-clinical user study with eleven medical experts. Results: Medical experts rated our application with a system usability scale score of 74.8 ± 15.9, which signifies above average, good usability and clinical acceptance. An average of 12.7 ± 6.6 minutes of training time was needed by physicians, before they were able to navigate the application without assistance. Conclusions: Our AR system is characterized by a slim and easy setup, short training time and high usability and acceptance. Therefore, it presents a promising, novel tool for visualizing head and neck cancer imaging and pre-surgical localization of target structures.